2017
DOI: 10.1556/0806.45.2017.038
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of seven novel Glu-A1mx alleles from Triticum monococcum ssp. monococcum

Abstract: Seven Glu-A1 m allelic variants of the Glu-A1 m x genes in Triticum monococcum ssp. monococcum, designated as 1Ax2.1 a , 1Ax2.1 b , 1Ax2.1 c , 1Ax2.1 d , 1Ax2.1 e , 1Ax2.1 f , and 1Ax2.1 g were characterized. Their authenticity was confirmed by successful expression of the coding regions in E. coli, and except for the 1Ax2.1 a with the presence of internal stop codons at position of 313 aa , all correspond to the subunit in seeds. However, all the active six genes had a same DNA size although their encoding su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…110 through SHW8A-Tb. Li et al (2016) suggested that such HMW-GS variations in ancestral species provided candidate genes for further wheat quality improvement. Durum variety Severina expressed a subunit 1Axnull, which was present in 2 families (G32 and G33), selected from SHW5A-Tb/Severina cross, while G34 possessed 1Ax2* inherited from T. boeoticum through SHW5A-Tb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…110 through SHW8A-Tb. Li et al (2016) suggested that such HMW-GS variations in ancestral species provided candidate genes for further wheat quality improvement. Durum variety Severina expressed a subunit 1Axnull, which was present in 2 families (G32 and G33), selected from SHW5A-Tb/Severina cross, while G34 possessed 1Ax2* inherited from T. boeoticum through SHW5A-Tb.…”
Section: Discussionmentioning
confidence: 99%
“…110 showed resistance to both investigated powdery mildew and leaf rust, thus being estimated as valuable resource for wheat improvement and involved in creation of several amphiploids. Li et al (2016) detected eight Glu-A1x alleles in T. monococcum ssp. monococcum, and five from them were novel (Glu-A1 m -b, Glu-A1 m -c, Glu-A1 m -d, Glu-A1 m -g and Glu-A1 m -h).…”
Section: Introductionmentioning
confidence: 98%
“…Sixty T. turgidum and 83 T. monococcum accessions with diverse geographic origins (Zhang et al ., 2008; Li et al ., 2016) were used in this study. Lines with PI or CItr prefixes were kindly provided by USDA-ARS, USA while AS lines were obtained from the Sichuan Agricultural University.…”
Section: Methodsmentioning
confidence: 99%
“…All 83 T. monococcum accessions used were T. monococcum ssp. monococcum (Zhang et al ., 2008; Li et al ., 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation